Competency-based education in three pilot programs : examining implementation and outcomes - Steele, Jennifer L.; Lewis, Matthew W.; Santibáñez, Lucrecia; Faxon-Mills, Susannah; Hamilton, Laura S.; Stecher, Brian M.; Rudnick, Mollie (RAND, 2014)
In 2011, the Bill & Melinda Gates Foundation created the Project Mastery grant program to support competency-based education initiatives in large school systems that serve a high proportion of disadvantaged youth. Competency-based education meets students where they are academically, provides students with opportunities for choice, and awards credit for evidence of learning, not for the time students spend studying a subject. The Foundation asked RAND to evaluate these efforts in terms of implementation, students' experiences, and student performance. This report presents final results from that evaluation, offering an overview of competency-based education and the Project Mastery grant projects and describing the implementation of competency-based educational features under each project. The report concludes with six lessons for policy, partnerships, and practice.